Taxonomic and Electrophoretic Studies of Selected Species of Ganoderma (Karst.) - Abdullah, Faridah (1996)
Ganoderma, the causal pathogen of Basal Stem Rot, is found in association with all major plantation crops in Malaysia, but the most severe debilitation caused is when they are found on oil palms. It is not known how many species/pathogenic types there are, whether a differential degree of virulence existed, and whether the fungus is host-specific. Ganoderma taxonomy is still controversial and could not effectively aid pathological considerations. This study was carried out to fulfill 4 main objectives. The first was to determine the diversity and percentage distribution of sporophore types found in association with oil palms. The second was to determine a means of inducing sporophore production under controlled conditions, starting from mycelial cultures. The third was to characterise the samples based on sporophore morphology, mycelial types and vegetative compatibility of isolates within and between groups. The fourth was to assess the relationship of Ganoderma within and between sampling groups using the Numerical Taxonomy Systematics computer programme based on Roger's Distance Measure (DJ The raw data were obtained from isozyme electrophoresis, using mycelial extracts. A morphological assessment showed a total of seven colour types found on oil palms and coconut stumps in West Malaysia. Four were recognised as G. boninense, G. miniatocinctum, G. chalceum and G. tornatum, but descriptions for three others (CT3, CT5 and CT7) could not be found and were assumed yet to be taxonomically annotated. Success with sp orophore induction techniques has aided morphological characterisation procedures in this study and its viability has introduced a potential basis for a further and more intensive conventional systematics investigations. Mycelial characterisation did not show any correlation with the variety of sporophore colours. Isozyme electrophoresis did not reciprocate the polymorphism exhibited by Ganoderma sporophores, but yielded important informations on distance relationships. Acid Phosphatase and Malate Dehydrogenase were good marker isozymes as they could distinguish successfully, isolates of palmhosts from isolates of tree-hosts. No similar marker-isozyme existed for isolates within the palm-hosts, although (with the exception of EGP series for Cholinesterase) no isolate from oil palm showed bands identical to the isolates from coconut stumps and vice versa. The resultant dendrogram based on Roger's Distance (D) showed three major clusters at 0.31, 0.48 and 0.66. The first major cluster divides the population into isolates of palm-hosts vs. tree-hosts. Results from numerical analysis showed that host type was a stronger basis for a close relationship, and that geographical origin and/or a common symptomology was less relevant.